ACADEMIC SUPERVISION OF THE HEAD OF THE MADRASAH IN INCREASING THE PEDAGOGIC COMPETENCE OF MTS TEACHERS AL-KHOIRIYAH BANYUASIN - Yopi Sumarlin; Fuad Abdurrahman; Abdurrahmansyah Abdurrahmansyah (Conciencia, 2022)
The teacher's pedagogic competence can develop well, and it is necessary to have supervision designed and implemented by the head of the madrasa. From the implementation of academic supervision, some factors can later support these activities and inhibiting factors. This type of research is classified as qualitative research. The aim is to examine and analyze how the supervision of the madrasah principal in the development of teacher pedagogic competence. The approach used in this research is a case study approach, with data collected by observation, interviews, and documentation studies. The results of this study concluded that academic supervision was carried out through three stages, namely the planning, implementation, and evaluation processes. The development of pedagogic competence for all ten teachers at MTs al-Khoiriyah Banyuasin is carried out by supervising the learning process in the classroom, helping to solve problems faced by teachers, improving infrastructure, and creating good communication and providing motivation. Supervision of madrasah principals is related to the pedagogic competence of teachers because supervision will form the ability of capable and professional teachers to implement learning.